A construção de significados atribuídos à morte de um ente querido e o processo de luto - Mazorra, Luciana (2009)
The present qualitative study aimed at to investigate the meaning-making of the grief process in adulthood, based on the Dual Process Model and Attachment Theory. Three case studies were carried out with women, between the ages of twenty five to fifty one years old, bereaved due to the death of loved ones in a period of time ranging from eleven months to one year and ten months before their participation in this research. The research data also includes the materials generated by semidirected interviews, the Original Romance Test (RO) and History of my Loss Test (HP). The central meanings found here were: I don t understand what happened; I´m responsible for the death; Someone is responsible for the death; The deceased is responsible for the death; I m not responsible for the death; God was responsible for the death; The death was God s punishment; I took the deceased place; The deceased deceived me and left me; I don t have emotional resources to survive to the loss; I must not feel anger; I grew up with the loss; I m strong; I don t know who I am; I want to live; I want to die; I was born after the loss; Having loved the deceased is comforting; The world is caring and trustworthy; The world is not caring and trustworthy; Death was humiliating; God forgave me. Related to these meanings were sense-making of the loss, identity change, transformation concerning the relationship with the deceased and the world and benefit finding, related to feelings, wishes and psychic mechanisms. The meaning construction was related to some factors: family dynamics; personality and attachment style; circumstances of death; kind of relationship with the deceased and social support. Among these factors, those that facilitate or jeopardize the meaning-making process were identified. The meanings reflect the grief process and being aware of them leads to the understanding of grief manifestations (feelings, behaviors, symptoms) and coping, and are related to elaboration processes or grief complication